2004
DOI: 10.1038/sj.ijir.3901256
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide–cyclic GMP pathway with some emphasis on cavernosal contractility

Abstract: Nitric oxide (NO) is formed from the conversion of L-arginine by nitric oxide synthase (NOS), which exists in three isoforms: neuronal (nNOS), endothelial (eNOS), and inducible (iNOS). nNOS is expressed in penile neurons innervating the corpus cavernosum, and eNOS protein expression has been identified primarily in both cavernosal smooth muscle and endothelium. NO is released from nerve endings and endothelial cells and stimulates the activity of soluble guanylate cyclase (sGC), leading to an increase in cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 96 publications
0
53
0
Order By: Relevance
“…[7][8][9][10] Some drugs such as inhibitors of PDE 5 or other vasodilators, which can promote the relaxation of corpus cavernosum smooth muscle, can be potentially used to treat ED. [11][12][13][14][15][16][17][18][19] It has been shown that there are many Chinese traditional herbals that can enhance sexual activity. [20][21][22][23][24] Recently, there is an increasing interest in investigating their effective components.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Some drugs such as inhibitors of PDE 5 or other vasodilators, which can promote the relaxation of corpus cavernosum smooth muscle, can be potentially used to treat ED. [11][12][13][14][15][16][17][18][19] It has been shown that there are many Chinese traditional herbals that can enhance sexual activity. [20][21][22][23][24] Recently, there is an increasing interest in investigating their effective components.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, decrease of free Ca 2ϩ in the sarcoplasm is caused mainly by the nitric oxide (NO)/cyclic guanosine monophosphate (cGMP)/cGMP-dependent protein kinase-1 (cGKI)/phosphodiesterase 5 (PDE5) pathway, followed by calmodulin dissociation from myosin light-chain kinase, leading to SMM dephosphorylation and subsequent SM relaxation (20). This signaling pathway has been indentified in human prostate and colocalization of ␣-actin with cGMP, and cGKI supports the role of this pathway in regulating prostatic SM contractility (71).…”
mentioning
confidence: 99%
“…It is well know that nitric oxide (NO) is the major mediator of endothelium-dependent relaxation in aorta (15,21,22), which is formed from the conversion of L-arginine by nitric oxide synthase (NOS) in endothelium cell and released. This endothelium -derived NO stimulates the activity of soluble guanylate cyclase (sGC) in smooth muscle cells, leading to an increase in cyclic guanosine-3',5'-monophosphate (cGMP) and finally to calcium depletion from the cytosolic space and vascular smooth muscle relaxation (15,(21)(22)(23). Various agonists such as NE (noradrenaline), phenylephrine, 5HT can stimulate the release of NO from the endothelium during vasocontractile response to them (9).…”
Section: Discussionmentioning
confidence: 99%